Effective In Vitro Clearance of Porphyromonas gingivalis by Fcα Receptor I (CD89) on Gingival Crevicular Neutrophils - Kobayashi, Tetsuo (American Society for Microbiology, 2001)
Porphyromonas gingivalis has been implicated as a causative pathogen in periodontitis. Immunotherapeutic approaches have recently been suggested to aid in the clearance of P. gingivalis from disease sites. Because antibody-Fc receptor (FcR) interactions play a role in the effector functions of polymorphonuclear neutrophils (PMN), we evaluated which FcR on PMN from gingival crevicular fluid (GCF) serves as an optimal target molecule for FcR-directed immunotherapy. GCF PMN and peripheral blood (PB) PMN from adult periodontitis patients were analyzed for their immunoglobulin G (IgG) and IgA FcR (FcγR and FcαR, respectively) expression and function by studying IgG- and IgA-mediated elimination of P. gingivalis. GCF PMN exhibited higher FcαRI and FcγRI levels and lower FcγRIIa and FcγRIIIb levels than PB PMN. Functional studies revealed that GCF PMN exhibited less of a capacity to phagocytose and kill IgG1-opsonized P. gingivalis than PB PMN. IgA1-mediated phagocytosis and killing capacity was, however, comparable between GCF PMN and PB PMN. In summary, these in vitro results document that FcαRI represents a candidate target for FcR-directed immunotherapy for the clearance of P. gingivalis.